2014
DOI: 10.1186/s12989-014-0055-3
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetics and effects of barium sulfate nanoparticles

Abstract: BackgroundNanoparticulate barium sulfate has potential novel applications and wide use in the polymer and paint industries. A short-term inhalation study on barium sulfate nanoparticles (BaSO4 NPs) was previously published [Part Fibre Toxicol 11:16, 2014]. We performed comprehensive biokinetic studies of 131BaSO4 NPs administered via different routes and of acute and subchronic pulmonary responses to instilled or inhaled BaSO4 in rats.MethodsWe compared the tissue distribution of 131Ba over 28 days after intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 45 publications
8
85
0
Order By: Relevance
“…For soluble NPs such as various metal oxides, it is important to understand particle dissolution to be able to distinguish between uptake and/or translocation of NPs, particle fragments or dissolved ions. A recent NP translocation study in rats demonstrated that it is of key relevance to perform such NP dissolution studies under in vivo -like conditions [24]. In this work, the fast clearance of inhaled BaSO 4 NPs did not correlate with its very low dissolution rate in phagolysosomal simulant fluid (PSF) [24], a proposed model of macrophage dissolution/clearance of particles.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For soluble NPs such as various metal oxides, it is important to understand particle dissolution to be able to distinguish between uptake and/or translocation of NPs, particle fragments or dissolved ions. A recent NP translocation study in rats demonstrated that it is of key relevance to perform such NP dissolution studies under in vivo -like conditions [24]. In this work, the fast clearance of inhaled BaSO 4 NPs did not correlate with its very low dissolution rate in phagolysosomal simulant fluid (PSF) [24], a proposed model of macrophage dissolution/clearance of particles.…”
Section: Resultsmentioning
confidence: 81%
“…A recent NP translocation study in rats demonstrated that it is of key relevance to perform such NP dissolution studies under in vivo -like conditions [24]. In this work, the fast clearance of inhaled BaSO 4 NPs did not correlate with its very low dissolution rate in phagolysosomal simulant fluid (PSF) [24], a proposed model of macrophage dissolution/clearance of particles. The authors conclude that the currently used cell-free in vitro dissolution studies either lack crucial constituents or do not adequately simulate the processes that facilitate particle dissolution and increase bioavailability.…”
Section: Resultsmentioning
confidence: 81%
“…Morfeld et al [16] concurred with the conclusion of the authors that particle surface area rather than volume or mass was the appropriate metric to confirm that both particle types are PSP particles; whereas Pauluhn [18] pointed to an enhanced dissolution of BaSO 4 when fitting the data of the accumulation phase. Indeed a recent study [20] in rats with inhalation and intratracheal instillation of nano-sized BaSO 4 reported that 95% of the retained lung burden of BaSO 4 was cleared within 34 days post-inhalation and that the retention halftime of instilled BaSO 4 was less than 10 days. This is significantly faster than a normal T½ of 60–80 days for both modes of BaSO 4 delivery to the lung.…”
mentioning
confidence: 99%
“…17 Experimental evidence has shown that barium sulfate nanoparticles cause lung injury and inflammation in rats. 18 During oxidative stress, the antioxidant mechanisms are Oberdorster et al 19 reported that the reduction of GSH and stimulation of LPO and ROS induce oxidative damage of cell components. ROS, lipid peroxidation, and SOD activity was increased, whereas glutathione level was less in BaONPs-treated L929 cells.…”
Section: Discussionmentioning
confidence: 99%